Measuring Biodiversity and Extinction—Present and Past. (18th September 2018) - Sigwart, Julia D; Bennett, K D; Edie, Stewart M; Mander, Luke; Okamura, Beth; Padian, Kevin; Wheeler, Quentin; Winston, Judith E; Yeung, Norine W
Abstract: How biodiversity is changing in our time represents a major concern for all organismal biologists. Anthropogenic changes to our planet are decreasing species diversity through the negative effects of pollution, habitat destruction, direct extirpation of species, and climate change. But major biotic changes—including those that have both increased and decreased species diversity—have happened before in Earth's history. Biodiversity dynamics in past eras provide important context to understand ecological responses to current environmental change. The work of assessing biodiversity is woven into ecology, environmental science, conservation, paleontology, phylogenetics, evolutionary and developmental biology, and many other disciplines; yet, the absolute foundation of how we measure species diversity depends on taxonomy and systematics. The aspiration of this symposium, and complementary contributed talks, was to promote better understanding of our common goals and encourage future interdisciplinary discussion of biodiversity dynamics. The contributions in this collection of papers bring together a diverse group of speakers to confront several important themes. How can biologists best respond to the urgent need to identify and conserve diversity? How can we better communicate the nature of species across scientific disciplines? Where are the major gaps in knowledge about the diversity of living animal and plant groups, and what are the implications for understanding potential diversity loss? How can we effectively use the fossil record of past diversity and extinction to understand current biodiversity loss?